The Values of Pancasila Student Profiles in Kartini's Novels and Their Relevance to Indonesian Language Learning in Elementary Schools - Nurhayati Nurhayati; Mukti Widayati; Nurnaningsih Nurnaningsih (JENIUS (Journal of Education Policy and Elementary Education Issues), 2025)
This study examines the values of the Pancasila Student Profile contained in the novel Kartini by Wiwid Prasetyo and their relevance to Indonesian language learning in elementary schools. The research aims to describe (1) the Pancasila Student Profile values presented in the novel and (2) their relevance to elementary Indonesian language teaching materials. This study employs a descriptive qualitative method. The data consist of quotations, phrases, and declarative sentences obtained from the novel and Character Education documents issued by the Ministry of Education and Culture. Data were collected through library research, document analysis, and note-taking, with purposive sampling used. Data validity was ensured through source and technique triangulation, while data were analyzed using the interactive analysis model of Miles and Huberman, including data collection, reduction, presentation, and conclusion drawing. The results show that the Kartini novel contains six dimensions of the Pancasila Student Profile: faith in God Almighty, global diversity, mutual cooperation, independence, creativity, and critical reasoning. These values are relevant to Indonesian language learning materials in elementary schools, particularly in fostering character values such as faith, diversity, cooperation, responsibility, leadership, and social care. The findings imply that novels can serve as effective learning media for integrating character education and strengthening the Pancasila Student Profile in elementary education.